Down-regulation of miR-517a and miR-517c promotes proliferation of hepatocellular carcinoma cells via targeting Pyk2 - Liu, Rui-Fang; Xu, Xiao; Huang, Jian; Fei, Qian-Lan; Chen, Fei; Li, Yan-Dong; Han, Ze-Guang (Cancer letters, 2013)
► Human microRNA microarray analysis was performed on 8 HCC cell lines treated by DNA demethylation agent and histone deacetylase inhibitor. ► The largest human miRNA gene cluster C19MC on chromosome 19 was triggered by these epigenetic modification agents. ► Functional screen of 43 miRNAs on C19MC revealed that both miR-517a and miR-517c can suppress HCC cell growth. ► Both miR-517a and miR-517c inhibited cell proliferation by blocking G2/M transition. ► PYK2 is a target of both miR-517a and miR-517c. Growing evidence indicates that some tumor suppressive miRNAs are subject to epigenetic modifications during carcinogenesis. Here, we found that a large miRNA cluster of C19MC was upregulated in HCC cells after combined treatment with DNA methylation inhibitor and histone deacetylase inhibitor. MiR-517a and miR-517c were strikingly different from the remaining 41 miRNAs in C19MC. Ectopic expression of MiR-517a and miR-517c inhibited cell proliferation by blocking G2/M transition, whereas down-regulation of miR-517a and miR-517c facilitated cell growth. We further showed Pyk2 is a target of miR-517a and miR-517c and both the miRNAs are downregulated in HCC samples. These data collectively suggest that down-regulation of both miR-517a and miR-517c contribute to HCC development through regulating Pyk2.